La documentación en el contrato de transporte aéreo de personas y de mercancías - Marco Arcalá, Luis Alberto (Pontificia Universidad Católica del Perú, 2021)
The need of documentation is evident in all different aspects and activities inside of air carriage of passengers and goods, including, of course, the contracts for the provision of this kind of services. However, it is also true that the most relevant documentary instruments in these contracts not only have their own peculiar features, but are also immersed in a process of evolution marked by various phenomena.  In this article, the author analyzes the main documentary in the contracts of air carriage of passengers and goods, with special focus on its legal character, functions, composition, way of working, among others. In the same way, he addresses the phenomenon of documental digitization and the effects the COVID-19 pandemic on the different aspects of air carriage. Lastly, he formulates a critical assessment in concerning with the future prospects of this field.

Es evidente la necesidad de documentación en todos los diferentes aspectos y actividades del transporte aéreo de personas y de mercancías, lo que, por supuesto, incluye los contratos que tienen por objeto la prestación de este tipo de servicios. Sin embargo, los principales títulos documentales presentes en estos contratos no solo cuentan con sus peculiares características, sino que además se hallan inmersos en un proceso de evolución marcado por diversos fenómenos.  En el presente artículo, el autor analiza los principales títulos documentales en los contratos de transporte aéreo de personas y de mercancías, haciendo especial énfasis en su naturaleza jurídica, funciones, estructura, funcionamiento, entre otros. De igual manera, aborda el fenómeno de la digitalización documental y los efectos de la pandemia del COVID-19 en los diferentes aspectos del transporte aéreo. Finalmente, formula una valoración crítica en relación con las perspectivas de futuro en este ámbito.
Documents in contracts of air carriage of passengers and goods
Keywords: Air and Space law; Air transport; Air transport contract; Transport documents; Air passenger rights; Derecho aeronáutico; Transporte aéreo; Contrato de transporte aéreo; Documentos de transporte; Derechos de los pasajeros aéreos; https://purl.org/pe-repo/ocde/ford#5.05.01